Sensibilidade a herbicidas e uso de gesso agrícola em sistema de produção consorciados com abacateiros e culturas anuais - Silva, Diogo Mendes da (2019)
The present work has as objective to evaluate the herbicide selectivity, the costs of production and use of agricultural plaster in a production system intercropped with annual crops, as well as to evaluate the effects of the treatments on the physical structure of the soil. Firstly, it was evaluated the sensitivity of avocado seedlings to the phytotoxic effects of herbicide application in post emergence. The experimental design was a randomized complete block with 4 replications and 8 treatments. Each experimental plot consisted of three avocado seedlings ranging from 70 cm to 1 m in height. Phytotoxicity and chlorophyll a, b, total and a / b ratio visual evaluations were performed. The Fluasifope-p-butyl and Imazetapir treatments have been shown to be the most promising for use in avocado orchard. The second work evaluated the production costs and economic viability of growing avocados intercropped with annual crops and application of agricultural plaster. The work was carried out in an area of 0.9 hectares. Consisting of 225 avocado trees arranged in rows of 25 plants each in a 5x8 spacing. A randomized block design with 4 replications was used, the treatments used were 4 doses of agricultural plaster in the plot (0, 3, 6 or 9 t.ha-1) and cultivation of annual species in consortium (Wheat, beans and corn). ) and fallow with brachiaria between the lines. The largest amount of initial investment in the treatment of 9 t / ha was efficient, eliminating the investment debt and promoting a profit of R $ 1,001.13 with two years of cultivation. The third work was carried out in an area of 0.9 hectares, aimed to evaluate the effects of different doses of agricultural plaster on soil physical attributes and the productivity of annual crops intercropped with an avocado orchard. A randomized complete block design with split plots was used, distributed in 4 doses of agricultural plaster in the plot (0, 3, 6 or 9 t.ha-1) and two types of cultivation (annual species and fallow with brachiaria). in the subplots, in a 4x2 factorial experimental scheme. The annual species cultivated in the experimental period of two years were wheat, beans and silage corn in a succession scheme. Fram evaluated soil physical attributes and annual crop yield. The gypsum influenced the improvement of the evaluated physical attributes of the soil and increased the productivity of silage beans and corn.